Leonor Espinoza de Menéndez´s Zarela. A feminist story: without education woman does not advance - Rojas Benavente, Lady (2013)
This research focuses on Leonor Espinoza de Menéndez´s novel, Zarela. A feminist story (1915?)raising the need to change the status of women in the early 20th century in Peru through legalrecognition of civic, educational and labour rights of women. The gender issues, ideologicalrepresentations of male and female characters and abusive relationships help understand thetraditional and misogynist society´s context that was backed by State, legal and cultural institutions inorder to maintain the status quo and social and sexual differences. The writer Espinoza emphasizesthe need for education of women so that she can develop and play a role at work autonomouslyand independently. Her equality feminism calls for urgent changes.